The Story of Elaeagia Resin (Mopa-Mopa), So Far - Richard Newman; Emily Kaplan; Maria Cecilia Álvarez-White (Heritage, 2023)
The unusual resin from some species of Elaeagia, a genus now found in certain parts of Central America and South America, was probably first utilized by native peoples in Colombia more than a thousand years ago. It became a crucial part of often elaborately decorated objects made in the southwestern city of Pasto in the colonial period, and it has continued to be used there up to the present, in which it is at the core of a local craft tradition. The resin was also utilized for about 300 years by the Inka, mainly to decorate qeros (ceremonial drinking cups). The resin is often referred to as mopa-mopa and, specifically in Colombia, as barniz de Pasto. The botany, chemistry, properties, and analysis of Elaeagia resin are reviewed, along with a brief survey of the history of its use.